Pertactin deficiency of Bordetella pertussis: Insights into epidemiology, and perspectives on surveillance and public health impact - Ulrich Heininger; Helena Martini; Jennifer Eeuwijk; Ivana Prokić; Adrienne P. Guignard; Elisa Turriani; Maurine Duchenne; Valérie Berlaimont (Human Vaccines & Immunotherapeutics)
Pertussis resurgence has been documented even in countries with high pediatric vaccine coverage. The proportion of Bordetella pertussis isolates not expressing pertactin (PRN) has increased in several countries where acellular pertussis (aP) vaccines are used. We systematically reviewed published literature up to July 2023 on PRN-negative B. pertussis isolates in MEDLINE and Embase with no geographical limitations, complemented with a gray literature search. An increase in the proportion of PRN-negative isolates was observed in countries where aP vaccines were used, while such isolates seem to be absent in countries using whole-cell pertussis vaccination. We reviewed the data supporting aP vaccine-driven evolution of B. pertussis, explored the effects of PRN deficiency on the clinical presentation of pertussis, summarized the evidence for preserved aP vaccine effectiveness, and proposed actions to further improve assessment of the clinical significance of PRN deficiency and its potential impact on pertussis prevention.